Issues involved in the phenotypic classification of orofacial clefts ascertained through a state birth defects registry for the north carolina cleft outcomes study. Issue 11 (6th August 2015) - Aylsworth, Arthur S.; Allori, Alexander C.; Pimenta, Luiz A.; Marcus, Jeffrey R.; Harmsen, Katherine G.; Watkins, Stephanie E.; Ramsey, Barry L.; Strauss, Ronald P.; Meyer, Robert E.
Abstract : Background: Epidemiologic studies involving birth defects are extremely sensitive to phenotype accuracy and precision. We devised a case review and classification protocol for a project to study school achievement in children with idiopathic, nonsyndromic orofacial clefts to improve the reliability of phenotypic classification from the statewide birth defects registry. Methods: Surveillance‐program abstraction data and medical records at the birth or treating hospitals were used when available. Exclusion criteria included: median cleft lip; Tessier cleft; premaxillary agenesis; presence of a recognizable syndrome, phenotype, association, or sequence (other than Robin sequence); clefts with other malformations not considered to be normal or common variants in the newborn; and cases with documented or suspected genetic or teratogenic causes. Results: Of 712 children identified with orofacial clefts, 153 were excluded, leaving 559 nonsyndromic orofacial cleft cases of unknown cause in the final study. These cases were grouped into the following clinically meaningful types: cleft lip with or without cleft alveolus; cleft lip and cleft palate; and cleft palate only. This review and classification process resulted in the elimination of 21.5% of the original cohort of identified cases, with most exclusions being due to suspected syndromic associations. Conclusion: Verbatim descriptions of the clinical findings are critical for accurate classification of diagnoses. This review process improved the precision of orofacial cleft phenotype classification for our study. Precision would have been further improved if all of the cases had verbatim descriptions of diagnoses and all medical records could have been reviewed by the classification team. Birth Defects Research (Part A) 103:899–903, 2015. © 2015 Wiley Periodicals, Inc.